Attention-based drivers, operational resilience, and operational efficiency: model development and empirical analysis - Essuman, Dominic (KNUST, 2026)
A doctoral thesis submitted to the Department of Supply Chain and Information Systems, Kwame Nkrumah University of Science and Technology School of Business, in partial fulfilment of the requirements for the award of Doctor of Philosophy in Logistics and Supply Chain Management